Gambaran story card dkk (diagnosa keperawatan keluarga) pada aplikasi Dikei (Diagnosa Keperawatan Indonesia) - Suwarno Suwarno; Sigid Nugroho Adhi (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Family nursing diagnosis is a clinical decision on family problems obtained from a family assessment and then analyzed so that action planning decisions and goals are in accordance with the problems and needs of the family. In this article, an overview of the DKK story card will be displayed in the DiKeI application. Nurses can use technology in the nursing care process, especially in nursing diagnoses because it is expected that time efficiency in the nursing care documentation process to clients is expected. Objective: To created the family nursing diagnosis android aplication Methods: The research metode used Agile Software with Exteme Programming. There are 6 stages of the XP development model, namely Exploration, Planning, Iteration, Production, Maintenance and End of the Cycle. Meanwhile, in presenting the data in this article, it only reaches the iteration stage of application development by stating the number and narrative of the sections on the DKK story card. Results: There are 10 story cards for Family Nursing diagnoses in this study as the basis for making the DiKeI application, with a characteristic boundary format followed by the subjective and objective data, then the possibility of a diagnosis will appear along with the etiology possibility, as a cause or risk factor for the diagnosis. Conclusion: The intellectual property rights of DKK application's story card have been received by the Indonesian Directorate General of Intellectual Property Rights, thus facilitating the application production process. It can be continued into the production process and combined with the design of the DiKeI application especifically with the Individual Nursing Diagnosis (DKI) story cards.